Uncommon site of prostatic adenocarcinoma metastasis thyroid cartilage - ENGÜR, CEREN ÖZGE; ÖZGÜVEN, SALİH; KESİM, SELİN; FİLİZOĞLU, NUH (My University, 2019)
Aim: Prostate cancer is the most common malignancy in men and tends to metastases to bone, lung, liver, pleura and adrenal glands. Herein we presented a case of prostate carcinoma with an atypical site of metastasis. Method: An 83-years-old male patient with a known diagnosis of prostate cancer and newly developed mass in the left lung was referred to fludeoxyglucose (FDG) positron emission tomography (PET)/computerized tomography (CT) and Ga-68 prostate membrane antigen (PSMA)/PET/CT. Results: FDG PET/CT demonstrated hypermetabolic mass located in apicoposterior segment of the left lung and multiple hypermetabolic metastatic lesions in skeletal system including the right side of the thyroid cartilage. Then, patient underwent Ga-68 PSMA PET/CT due to an increase in prostate-specific antigen level (12.39 ng/mL). Ga-68 PSMA PET/CT revealed PSMA accumulation in the mass located in left lung, intense PSMA uptake in the prostatic gland and increased uptake in the widespread metastatic lesions of skeletal system involving the right side of the thyroid cartilage. Conclusion: Ga-68 PSMA is a useful tool for evaluating the distant and unexpected metastases of prostate cancer. Cartilaginous tissue is a resistant site for metastasis because its rich structure of protease inhibitors prevents the destruction of extracellular matrix components. In this patient with advanced stage prostate cancer, both FDG and PSMA uptake were observed in the thyroid cartilage metastasis.
Keywords: Thyroid Cartilage; prostate Cancer; FDG PET/CT; Ga-68 PSMA PET/CT